In-vitro antidermatophytic activity of methanolic fraction from entada spiralis ridl. stem bark and its bioautographic profile - Harun, Aiza; Mat So'ad, Siti Zaiton; Mohd Hassan, Norazian; Che Mohd Ramli, Neni Kartini (Universiti Putra Malaysia Press, 2014)
This study was performed to evaluate the antifungal activities of the methanolic fractions from the stem bark of Entada spiralis Ridl. against human dermatophytes and yeast-like fungus in in vitro. Three types of human dermatophytes and one yeast-like fungus namely Trichophyton mentagrophytes ATCC 9533, Microsporum gypseum ATCC 24102, Trichophyton tonsurans ATCC 28942, and Candida glabrata ATCC 66032 were tested against the methanolic fractions labelled as FA1, FA4 and FA5. First, the activities of antifungal were studied by disc diffusion method and broth micro dilution method. Second, we used an agar overlay bioautography assay to reveal antidermatophytic compounds of methanolic fractions. T.mentagrophytes, T.tonsuran and M.gypseum were susceptible towards all tested fractions in a concentration-dependent manner whereas C.glabrata was resistant. Fraction FA1 at a concentration of 400 mg/mL was found to exhibit highest antifungal activity with inhibition zone diameter of 22mm (T.mentagrophytes). FA1 showed MIC at 0.097 mg/mL while the MIC value for FA4 and FA5 were 3.12 mg/ml and 1.56 mg/ml respectively. Nystatin was used as standard antifungal drug and served as positive control. A garoverlay bioautography assay results showed that most of the bioactive compounds were 3 found in FA1. Based on these findings, it can be concluded that the stem bark extracts of E. spiralis can be a future source of potent natural antimicrobial drugs for superficial skin diseases.